Impaired Autophagic Flux in Skeletal Muscle of Plectin‐Related Epidermolysis Bullosa Simplex With Muscular Dystrophy - Michaela M. Zrelski; Margret Eckhard; Petra Fichtinger; Sabrina Hösele; Andy Sombke; Leonid Mill; Monika Kustermann; Wolfgang M. Schmidt; Fiona Norwood; Ursula Schlötzer‐Schrehardt; Gerhard Wiche; Rolf Schröder; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Plectin, a multifunctional cytolinker and intermediate filament stabilizing protein, is essential for muscle fibre integrity and function. Mutations in the human plectin gene (PLEC) cause autosomal recessive epidermolysis bullosa simplex with muscular dystrophy (EBS‐MD). The disorganization and aggregation of desmin filaments in conjunction with degenerative changes of the myofibrillar apparatus are key features in the skeletal muscle pathology of EBS‐MD. We performed a comprehensive analysis addressing protein homeostasis in this rare protein aggregation disease by using human EBS‐MD tissue, plectin knock‐out mice and plectin‐deficient cells. Methods Protein degradation pathways were analysed in muscles from EBS‐MD patients, muscle‐specific conditional plectin knockout (MCK‐Cre/cKO) mice, as well as in plectin‐deficient (Plec−/−) myoblasts by electron and immunofluorescence microscopy. To obtain a comprehensive picture of autophagic processes, we evaluated the transcriptional regulation and expression levels of autophagic markers in plectin‐deficient muscles and myoblasts (RNA‐Seq, qRT‐PCR, immunoblotting). Autophagic turnover was dynamically assessed by measuring baseline autophagy as well as specific inhibition and activation in mCherry‐EGFP‐LC3B‐expressing Plec+/+ and Plec−/− myoblasts, and by monitoring primary Plec+/+ and Plec−/− myoblasts using organelle‐specific dyes. Wild‐type and MCK‐Cre/cKO mice were treated with chloroquine or metformin to assess the effects of autophagy inhibition and activation in vivo. Results Our study identified the accumulation of degradative vacuoles as well as LC3‐ and SQSTM1‐positive patches in EBS‐MD patients, MCK‐Cre/cKO mouse muscles and Plec−/− myoblasts. The transcriptional regulation of ~30% of autophagy‐related genes was altered, and protein levels of downstream targets of the autophagosomal degradation machinery were elevated in MCK‐Cre/cKO muscle lysates (e.g., LAMP2, BAG3 and SQSTM1 to ~160, ~150 and ~140% of controls, respectively; p < 0.05). Autophagosome turnover was compromised in mCherry‐EGFP‐LC3B‐expressing Plec−/− myoblasts (~40% reduction in median red:green ratio, reduced puncta number, smaller puncta; p < 0.01). By labelling autophagic compartments with CYTO‐ID dye or lysosomes with LYSO‐ID, we found reduced signal intensities in primary Plec−/− cells (p < 0.001). Treatment with chloroquine led to drastic swelling of autophagic vacuoles in primary Plec+/+ myoblasts, while the swelling in Plec−/− cells was moderate, establishing a defect in their autophagic clearance. Chloroquine treatment of MCK‐Cre/cKO mice corroborated that loss of plectin coincides with impaired autophagic clearance, while metformin amelioratively induced autophagic flux. Conclusions Our work demonstrates that the characteristic protein aggregation pathology in EBS‐MD is linked to an impaired autophagic flux. The obtained results open a new perspective on the understanding of the protein aggregation pathology in plectin‐related disorders and provide a basis for further pharmacological intervention.